mTOR Suppresses Macroautophagy During Striatal Postnatal Development and Is Hyperactive in Mouse Models of Autism Spectrum Disorders - Lieberman, Ori J.; Cartocci, Veronica; Pigulevskiy, Irena; Molinari, Maya; Carbonell, Josep; Broseta, Miguel Bellés; Post, Michael R.; Sulzer, David; Borgkvist, Anders; Santini, Emanuela (Frontiers in Cellular Neuroscience, 2020)
Macroautophagy (hereafter referred to as autophagy) plays a critical role in neuronal function related to development and degeneration. Here, we investigated whether autophagy is developmentally regulated in the striatum, a brain region implicated in neurodevelopmental disease. We demonstrate that autophagic flux is suppressed during striatal postnatal development, reaching adult levels around postnatal day 28 (P28). We also find that mTOR signaling, a key regulator of autophagy, increases during the same developmental period. We further show that mTOR signaling is responsible for suppressing autophagy, via regulation of Beclin-1 and VPS34 activity. Finally, we discover that autophagy is downregulated during late striatal postnatal development (P28) in mice with in utero exposure to valproic acid (VPA), an established mouse model of autism spectrum disorder (ASD) VPA-exposed mice have deficits in striatal neurotransmission and social behavior. Correction of hyperactive mTOR signaling in VPA-exposed mice restores social behavior. These results demonstrate that neurons coopt metabolic signaling cascades to developmentally regulate autophagy and provide additional evidence mTOR-dependent signaling pathways represent pathogenic signaling cascades in ASD mouse models that are active during specific postnatal windows.